(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2018)
It has been established that the housing rights of internally displaced persons are based on the International Covenant on Economic, Social and Cultural Rights, the United Nations Guidelines on Internal Displacement, General Comment No. 7: The Right to Affordable Housing (Article 11 (1) of the Covenant) of the UN Committee on Economic, Social and Cultural Rights and National Legislation. It has been determined that the specificity of housing rights of internally displaced persons lies in their legal regulation and content. This is due to the fact that individuals have undergone a forced eviction, which occurred outside their will, and therefore their housing rights need to be restored. The list of housing rights of internally displaced persons has been offered. It has been established that the housing rights of internally displaced persons are a special category that exists along with such groups of housing rights as housing rights of children and housing rights of persons with disabilities. The housing rights of internally displaced persons are the rights of persons who were forced to expel as a result of an armed conflict and were forced to leave their own homes. These rights include: the right to provide temporary housing for one year; the right to receive social housing for permanent residence; the right to protection of housing rights; the right to return to their own homes; the right to change the place of residence after the internal movement; the right to return a home; the right to compensation in case of destruction of housing or other circumstances that make it impossible to return; the right to live in safe housing. Housing rights of internally displaced persons include the rights enshrined in the Art. 47 of the Constitution of Ukraine. Consequently, the housing rights for internally displaced persons are a special category that exists along with such groups of housing rights as housing rights of children, housing rights of people with disabilities. It has been concluded that, despite the fact that the right to housing of internally displaced persons is declared by the norms of public law, the mechanism of realization of the housing rights is determined by the norms of private law.